2020
DOI: 10.1523/eneuro.0170-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Fear Deficits in HypomyelinatedTpppKnock-Out Mice

Abstract: Oligodendrocytes in the central nervous system (CNS) produce myelin sheaths that insulate axons to facilitate efficient electrical conduction. These myelin sheaths contain lamellar microtubules that enable vesicular transport into the inner sheath. Mechanistically, oligodendrocytes rely on Golgi outpost organelles and the associated protein tubulin polymerization promoting protein (TPPP) to nucleate or form new microtubules outside of the cell body. Consequently, elongation of lamellar microtubules is defectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Inflammatory and demyelination are known to cause several pathological hallmarks, including axonal loss, gray matter pathology, and immune cell infiltrations in RRMS patients; however, PMS patients do not exhibit an obviously active immunization status. Current evidences proves that the methylation of m6A RNA is highly associated with immune recognition, the activation of innate and adaptive immune responses, and cell fate decisions [ 32 ]. Thus, the extent of total m6A RNA methylation was relatively higher in patients with RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory and demyelination are known to cause several pathological hallmarks, including axonal loss, gray matter pathology, and immune cell infiltrations in RRMS patients; however, PMS patients do not exhibit an obviously active immunization status. Current evidences proves that the methylation of m6A RNA is highly associated with immune recognition, the activation of innate and adaptive immune responses, and cell fate decisions [ 32 ]. Thus, the extent of total m6A RNA methylation was relatively higher in patients with RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the behavior of TPPP/25 KO mice, their anxiety behavior has been similar as in the case of wild type mice, however, they lack fear responses. Deficits in fear-conditioning, which is a memory dependent task, as well as in spatial memory tests support possible short-term memory defects [74]. Experiments with TPPP/p25 KO mice that exhibit hypomyelination with aberrant myelin sheaths and motor coordination deficits have suggested that microtubule nucleation outside the cell body at Golgi outposts by TPPP/p25 is critical for the elongation of the myelin sheath [73].…”
Section: Tppp/p25 a Multifunctional Microtubule Associated Proteinmentioning
confidence: 97%
“…Oligomerization/aggregation of SYN was found to induce deficits in synaptic transmission and hippocampal neurogenesis, which may contribute to the appearance of cognitive deficits. Short-term memory defects have also been observed in TPPP/p25 KO mice, which exhibit hypomyelination [73,74]. Recently it has been proposed that OLGs and myelin sheaths play crucial roles in memory and learning [72].…”
Section: Innovative Strategy For Pd and Msa Therapymentioning
confidence: 99%
“…In oligodendrocytes, microtubules play important roles in building the structure of oligodendrocyte branches and myelin sheaths ( Fu et al, 2019 ) as well as in transporting mRNA and other cargos ( Carson et al, 1997 ; Herbert et al, 2017 ). Loss of the microtubule nucleation protein TPPP (tubulin polymerization promoting protein) results in shorter and thinner myelin sheaths as well as behavioral defects in motor coordination ( Fu et al, 2019 ) and in innate and memory-dependent fear responses ( Nguyen et al, 2020 ).…”
Section: Cytoskeletal Proteinsmentioning
confidence: 99%